Modelagem computacional das túnicas cardíacas para processamento e controle de qualidade - Neves, Leandro Alves [UNESP]; Fiocco, Daniel Luis; Godoy, Moacir Fernandes de (My University, 2011)
This paper considers a study of the anatomical features of the cardiac system and a three-dimensional model of the different tunics that comprise the heart wall, for processing and quality control of radiological images. The structures are built by the layer overlapping method, where a layer can be understood as a slice of the three-dimensional object. The pericardium, myocardium and endocardium were represented with three-dimensional cylinders and hexagons. The spatial arrangement of the cardiac system is determined by an background image of a real model, which values are defined according to the shape of the region and on the anatomical patients characteristics. The results are significant, considering the anatomical structures details, as well as the representation of the thicknesses of the regions of the heart wall. The validation of the anatomical model was accomplished through comparisons with dimensions obtained from a real model and allows verifying that the model is appropriate. The degree of representation will allow the verification of the influence of radiological parameters, morphometric peculiarities and stage of the diseases on the quality of the images, as well as on the performance of the Computer-Aided Diagnosis (CAD).

Este trabalho considera um estudo das características anatômicas do sistema cardíaco e um modelo tridimensional de diferentes túnicas que compõem a parede do coração, para processamento e controle de qualidade de imagens radiológicas. As estruturas são construídas pelo método de sobreposição de camadas, onde uma camada pode ser entendida como uma fatia do objeto tridimensional. O pericárdio, miocárdio e endocárdio foram representados com cilindros e hexágonos. A organização espacial do sistema cardíaco é determinada por uma imagem de fundo, obtida de um modelo real. Os valores para as estruturas são definidos de acordo com a região e pelas características anatômicas dos pacientes. Os resultados são significativos, por considerar detalhes anatômicos de estruturas, como a representação das diferentes espessuras presentes na parede cardíaca. A validação do modelo anatômico foi realizada através de comparações com as dimensões obtidas a partir de um modelo real e permite verificar que o modelo é adequado. O nível de representação permitirá testar as influências de parâmetros radiológicos, particularidades anatômicas e estágios de doenças na qualidade de imagens, bem como o desempenho de sistemas de auxílio ao diagnóstico (SAD).
Computational modeling of cardiac tunics for processing and quality control
Keywords: radiologia; controle de qualidade; interpretação de imagem assistida por computador; ensino; coração; radiology; quality control; computer-assisted image interpretation; teaching; heart